Aberrant Muscle Antigen Exposure in Mice Is Sufficient to Cause Myositis in a Treg Cell–Deficient Milieu. Issue 12 (27th November 2013) - Young, Nicholas A.; Sharma, Rahul; Friedman, Alexandra K.; Kaffenberger, Benjamin H.; Bolon, Brad; Jarjour, Wael N.
Abstract : Objective: Myositis is associated with muscle‐targeted inflammation and is observed in some Treg cell–deficient mouse models. Because an autoimmune pathogenesis has been strongly implicated, the aim of this study was to investigate the hypothesis that abnormal exposure to muscle antigens, as observed in muscle injury, can induce autoimmune‐mediated myositis in susceptible hosts. Methods: FoxP3 mutant (scurfy) mice were mated to synaptotagmin VII (Syt VII) mutant mice, which resulted in a new mouse strain that combines impaired membrane resealing with Treg cell deficiency. Lymphocyte preparations from double‐mutant mice were adoptively transferred intraperitoneally, with or without purified Treg cells, into recombination‐activating gene 1 (RAG‐1)–null recipients. Lymph node cells from mice with the FoxP3 mutation were transferred into RAG‐1–null mice either 1) intraperitoneally in conjunction with muscle homogenate or purified myosin protein or 2) intramuscularly with or without cotransfer of purified Treg cells. Results: FoxP3‐deficient mouse lymph node cells transferred in conjunction with myosin protein or muscle homogenate induced robust skeletal muscle inflammation. The infiltrates consisted predominantly of CD4+ and CD8+ T cells, a limited number of macrophages, and no B cells. Significant inflammation was also seen in similar experiments using lymph node cells from FoxP3/Syt VII double‐mutant mice but was absent in experiments using adoptive transfer of FoxP3 mutant mouse cells alone. The cotransfer of Treg cells completely suppressed myositis. Conclusion: These data, derived from a new, reproducible model, demonstrate the critical roles of Treg cell deficiency and aberrant muscle antigen exposure in the priming of autoreactive cells to induce myositis. This mouse system has multifaceted potential for examining the interplay in vivo between tissue injury and autoimmunity.